2020
DOI: 10.3390/nu12040914
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of High-Insulin-Induced Skeletal Muscle Cell Insulin Resistance by Resveratrol Is Linked to Activation of AMPK and Restoration of GLUT4 Translocation

Abstract: Insulin resistance, the hallmark of type 2 diabetes mellitus (T2DM), is linked to hyperinsulinemia, which develops to counterbalance initial peripheral hormone resistance. Studies indicate that chronically elevated levels of insulin lead to skeletal muscle insulin resistance by deregulating steps within the insulin signaling cascade. The polyphenol resveratrol (RSV) has been shown to have antidiabetic properties in vitro and in vivo. In the present study, we examined the effect of RSV on high insulin (HI)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 77 publications
1
42
1
Order By: Relevance
“…Previous studies performed in L6 muscle cells in vitro [ 8 , 29 , 37 ] and rat muscle tissue in vivo [ 38 ] indicated that increased serine (ser 307 and ser 636/639 ) phosphorylation of IRS-1 leads to impairments within the insulin signaling cascade, resulting in insulin resistance. Hence, we examined the effects of palmitate and RSV on serine phosphorylation and expression of IRS-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies performed in L6 muscle cells in vitro [ 8 , 29 , 37 ] and rat muscle tissue in vivo [ 38 ] indicated that increased serine (ser 307 and ser 636/639 ) phosphorylation of IRS-1 leads to impairments within the insulin signaling cascade, resulting in insulin resistance. Hence, we examined the effects of palmitate and RSV on serine phosphorylation and expression of IRS-1.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation/activation of AMPK in muscle cells was observed in response to contraction/exercise and exposure to chemicals that inhibit mitochondrial adenosine triphosphate (ATP) production, such as 2,4-dinitrophenol (DNP) [ 21 ]. Furthermore, there are several compounds that activate AMPK, including metformin [ 22 ], thiazolidineones [ 23 ], salicylate [ 24 ], and polyphenols, such as quercetin [ 25 ], berberine [ 26 ], and resveratrol [ 27 , 28 , 29 ]. Recently, AMPK activators have been considered to be a novel and attractive prophylactic or treatment strategy against insulin resistance and T2DM [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myotubes from T2D donors displayed fewer cycling rhythmic genes as compared to myotubes from NGT donors and the rhythmic genes in NGT were significantly associated with the rhythmic genes in T2D (Figure 1B, Fisher exact test, p=3.91e- 58). To induce acute insulin resistance and partly mimic a T2D milieu (Vlavcheski et al, 2020), myotubes from NGT and T2D donors were treated with high glucose and insulin (50 nM insulin, 25 mM glucose) for 24 hours prior to serum shock. High concentration glucose and insulin treatment reduced the number of cycling genes in myotubes from both T2D and NGT donors (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…To achieve energy balance under long-term ES, yaks regulated fat metabolism by the expression of the downstream genes involved in AMPK signaling [ 49 ], as shown in Figure 4 . The expression of the SLC2A3 ( q < 0.05) and SLC2A4 ( q < 0.01) genes was downregulated in the subcutaneous fat of the yaks under ES, which indicated that less GLU from grass was translated into subcutaneous fat, and the muscles and organs could obtain limited GLU [ 50 ].…”
Section: Discussionmentioning
confidence: 99%